2022
DOI: 10.3390/jcm11206002
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Bicuspid Aortopathy and Aortic Dilatation

Abstract: (1) Background: Bicuspid aortic valve (BAV) is the most frequent congenital cardiac disease. Alteration of ascending aorta diameter is a consequence of shear stress alterations due to haemodynamic abnormalities developed from inadequate valve cusp coaptation. (2) Objective: This narrative review aims to discuss anatomical, pathophysiological, genetical, ultrasound, and radiological aspects of BAV disease, focusing on BAV classification related to imaging patterns and flux models involved in the onset and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 171 publications
0
7
0
Order By: Relevance
“…Aortopathy refers to the progressive dilatation of the ascending aorta and is defined as an indexed maximal aortic diameter exceeding 21 mm/m 2 of the body surface area (BSA) [ 11 ]. Ascending aortic dilation configurations were slightly modified from the Fazel classification, which was assigned to four types depending on whether the segment of the vessel was exclusively or predominantly involved in dilatation: normal aorta; type 1, isolated dilation of the ascending aorta root at the level of the sinus of Valsalva [ 12 ]; type 2, middle ascending dilatation at the level of the tubular ascending portion; and type 3, combined dilatation of the aortic root and mid-ascending aorta ( Figure 3 ) [ 12 ]. Aortic aneurysms are defined as those with dimensions greater than 50 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Aortopathy refers to the progressive dilatation of the ascending aorta and is defined as an indexed maximal aortic diameter exceeding 21 mm/m 2 of the body surface area (BSA) [ 11 ]. Ascending aortic dilation configurations were slightly modified from the Fazel classification, which was assigned to four types depending on whether the segment of the vessel was exclusively or predominantly involved in dilatation: normal aorta; type 1, isolated dilation of the ascending aorta root at the level of the sinus of Valsalva [ 12 ]; type 2, middle ascending dilatation at the level of the tubular ascending portion; and type 3, combined dilatation of the aortic root and mid-ascending aorta ( Figure 3 ) [ 12 ]. Aortic aneurysms are defined as those with dimensions greater than 50 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The genetic theory of bicuspid aortopathy proposes that genetic abnormalities alter the development and function of the aortic valve and aorta, predisposing patients to BAV and aortic dilation. Within the last decade, research has identified candidate genes, transcription factor enzymes, metabolites, and signaling pathways implicated in abnormal aortic development and associated with aortic dilation [34][35][36][37].…”
Section: Genetic and Molecular Biomarkersmentioning
confidence: 99%
“…BAV-associated aortic dilatation can be classified into three types [ 25 ]. Type 1, the most common type, involves the dilatation of the aortic root, tubular ascending aorta, and proximal arch.…”
Section: Bav-related Aortic Wall Abnormalitiesmentioning
confidence: 99%